Comparative Study of Heavy Metals from Rivers Around Ramnicu Valcea and Craiova Chemical Platforms from Romania - Mladin, Cristian; Preda, Anisoara; Stefanescu, Ioan; Barbu, Cristina (Asian Journal of Chemistry, 2010)
In this paper, the analysis of heavy metals from Olt river around Ramnicu Valcea chemical platform and from Jiu river around Craiova chemical platform during three months before and after industrial zone are presented.